2017
DOI: 10.1016/j.ijpam.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cystic adenomatoid malformation

Abstract: Congenital pulmonary airway malformation of the lung is a rare lesion that commonly affects the lower respiratory tract, which manifests as progressive respiratory distress in the neonatal period. This case is highlighted to raise awareness of the variable evolving morphological and radiological appearance of this entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In some cases, CCAM lesions gradually became smaller or even disappeared at the later stage of pregnancy[ 20 ]. More than 15% of CCAM lesions can disappear after birth[ 21 ]. In this study, postnatal CT found no lesions in five cases, macrocystic CCAM was confirmed in four cases, and microcystic CCAM was confirmed in one case, with a lesion disappearance rate of 16.1% (5/31).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, CCAM lesions gradually became smaller or even disappeared at the later stage of pregnancy[ 20 ]. More than 15% of CCAM lesions can disappear after birth[ 21 ]. In this study, postnatal CT found no lesions in five cases, macrocystic CCAM was confirmed in four cases, and microcystic CCAM was confirmed in one case, with a lesion disappearance rate of 16.1% (5/31).…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, Stocker et al 14,15 classified CCAM into three types, type 1, 2, and 3, depending on the characteristics of the mass and source of the tissue. Type 1 originates from distal bronchus tissue or proximal bronchiole >2 cm in diameter and has multiple thin-wall cysts lined with a ciliated pseudostratified epithelium.…”
Section: Congenitalmentioning
confidence: 99%
“…6 Then, in 2002, Stocker added two more types of CCAM classification: types 0 and 4. 14 Type 0 arises from tracheal or bronchus tissue, while type 4 arises from alveolar tissue. CCAM has the potential to develop into malignancy, especially in CCAM type 4.…”
Section: Congenitalmentioning
confidence: 99%
“…Congenital cystic bronchiectasis is thought to be the result of developmental arrest. This may result in cyst formation, retention of fluid or air, and the risk of subsequent infection [1]. Congenital cystic bronchiectasis has been found almost exclusively in infants and young children [2,3] and also has been reported accompanying other congenital anomalies [4], or in patients with deficiency of bronchial cartilages.…”
Section: Introductionmentioning
confidence: 99%